Natural variability of essential oil and antioxidants in the medicinal plant Turnera diffusa - Urbizu González, Ana Lucía; Castillo Ruiz, Octelina; Martínez Ávila, Guillermo Cristian Guadalupe; Torres Castillo, Jorge Ariel (2017)
Objective: To evaluate differences in yield and composition of the essential oil and antioxidant contents in Turnera diffusa plants from localities in central region of Tamaulipas. Methods: Samples were collected in Tamaulipas, Mexico in the arid zone. Essential oil was obtained through steam distillation and analyzed using GC–MS. Polyphenol contents, antioxidant activities using ABTS and ferric reducing antioxidant power (FRAP) methods also were evaluated. Results: A total of 21 compounds were identified in the essential oils; nevertheless, only Eucalyptol, 1,4-Methanocycloocta[d]pyridazine, 1,4,4a,5,6,9,10,10a-octahydro-11,11- dimethyl-, (1`a,4`a,4a`a,10a`a) y Ethanone, 1-(1,3-dimethyl-3-cyclohexen-1-yl) were detected in the three sites. Highest contents were registered in the sample from Padr´on y Ju´arez with phenolic content of 33.85 mg GAE/g of dry material and antioxidant activities with ABTS 72.32% and with FRAP 21.33 mg GAE/g of dry material. Statistical differences were observed in essential oil, phenolics and antioxidants contents between populations. Conclusions: Results suggest that climatic differences and origin influence the phytochemicals in the medicinal plant Turnera diffusa, and thus, it is worth to consider such effects for industrial and medicinal purposes.